Analisis Pengaruh Praktik Manajemen Sumber Daya Manusia Terhadap Kinerja Guru (Studi di SDN Tanjungrejo Kota Malang) - Alfian Ahmad; Pardiman Pardiman; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study was conducted to analyze the effect of recruitment, selection, and training on teacher performance (at SDN Tanjungrejo Malang City). This research is a quantitative research that aims to develop and use theories and hypotheses related to research. Arikunto's theory is used for sampling with a population of less than 100. Therefore the entire population is taken as a sample. The sample in this study included all 77 teachers at SDN Tanjungrejo. Based the results of t test, it was found the recruitment variable (X1), which has a significant influence on teacher performance. Next Selection (X2), which has a significant effect on Teacher Performance, And Training (X3) which has a significant influence on Teacher Performance. The training variable has the largest t value. So that the training variable has a dominant influence on teacher performance. Keywords: Teacher Performance, Recruitment, and Training